Apparatus Career Development Result of Structural to Functional Equalization - Susanto, Yohanes (Golden Ratio of Human Resource Management, 2024)
This study examines the career development of government civil servants in the implementation of the policy of equalizing structural positions into functional positions and how the preparation of supporting factors and obstacles faced in the career development of the apparatus because of equalizing positions. The study employed a qualitative descriptive research method, with data collection through interviews, observation, and documentation of 11 informants in 4 regional apparatus of the city of Lubuklinggau, South Sumatra, Indonesia. The findings suggest that the equalization policy aimed at promoting the career progression of local government officers has not been fully effective. The other problems found are the ability of individual apparatus to collect credit numbers as proof of performance, mismatches of qualifications and competencies of positions, and work mechanisms that have not been adjusted after the equalization of positions. The recommendations of this study require adjustments to the work system, competency mapping, and priority training maps, as well as the preparation of counseling services for the apparatus resulting from the equalization of positions.